The Baltic states and the great powers : foreign relations ; 1938 - 1940 - Crowe, David M. (Westview Press, 1993)
This is the first complete account of the diplomatic relations and military steps leading to Estonia's, Latvia's, and Lithuania's forcible absorption into the USSR in 1940. David Crowe - making use of recently opened archival sources - traces the Baltic states' relations with the Soviet Union, Germany, Poland, Great Britain, France, and with one another from 1917-1940. He starts with an overview of 1917-1936 and then offers a detailed description of the diplomatic maneuvering that marked Europe's collective slide toward war. Crowe covers the Sudeten and Memel crises involving German communities in 1938, the German-Soviet Pact in August 1939, the mutual assistance pacts between the Baltic states and the USSR, the Baltic German migration, Soviet use of Estonia's military installations during their assault on Finland, and the subsequent Soviet occupation of the Baltic states. The story ends with the election of new, Soviet-sponsored legislatures that sought admission into the USSR as Soviet republics in 1940 - a step that most Western countries never recognized and one that the Baltic states finally reversed when they regained their independence fifty-one years later in August 1991.